Incidence of small bowel neoplasia in Lynch syndrome assessed by video capsule endoscopy - Haanstra, Jasmijn F.; Al-Toma, Abdul; Dekker, Evelien; Vanhoutvin, Steven A.L.W; Nagengast, Fokko M.; Mathus-Vliegen, Elisabeth M.; van Leerdam, Monique E.; de Vos tot Nederveen Cappel, Wouter H.; Veenendaal, Roeland A.; Cats, Annemieke; Sanduleanu, Silvia; Vasen, Hans F.A.; Kleibeuker, Jan H.; Koornstra, Jan J. (Endoscopy International Open, 2017)
Background and study aims Lynch syndrome (LS) patients have an increased risk of small bowel cancer. The question is whether surveillance will lead to early detection of (pre)malignant lesions. We recently reported on prevalence of small bowel neoplasia (SBN) in LS patients as assessed by video capsule endoscopy (VCE). The aim of this prospective study was to determine the incidence of SBN.Patients and methods Asymptomatic LS patients who underwent a VCE were invited to undergo a second VCE procedure 2 years later. If abnormalities or polypoid lesions larger than 1 cm were detected, subsequent endoscopic procedures were performed.Results A total of 155 (78 %) of the initial 200 patients underwent a second VCE procedure after a mean of 2.2 (range 1 – 6) years. In 17 of the 155 (11 %) patients possibly significant lesions were detected, which required further investigation by means of gastroduodenoscopy (n = 8) or balloon-assisted endoscopy (n = 9). These procedures revealed no SBN.Conclusion No SBN was found after 2 years. Surveillance of the small bowel by VCE does not seem to be warranted in asymptomatic LS patients. This study was registered in the Clinical Trials.gov registry with identifier NCT00898768.